Wγ production and limits on anomalous WWγ couplings in pp̄ collisions at √s=1.96TeV - Abazov, V. M. (2011)
We measure the cross section and the difference in rapidities between photons and charged leptons for inclusive W(→lν)+γ production in eγ and μγ final states. Using data corresponding to an integrated luminosity of 4.2fb -1 collected with the D0 detector at the Fermilab Tevatron Collider, the measured cross section times branching fraction for the process pp̄→Wγ+X→lνγ+X and the distribution of the charge-signed photon-lepton rapidity difference are found to be in agreement with the standard model. These results provide the most stringent limits on anomalous WWγ couplings for data from hadron colliders: -0.4<Δκ γ<0.4 and -0. 08<λ γ<0.07 at the 95% C.L. © 2011 American Physical Society.